Probability expression for changeable and changeless uncertainties: an implicit test - Wang, Yun; Du, Xue-Lei; Rao, Li-Lin; Li, Shu (Frontiers in Psychology, 2014)
‘Everything changes and nothing remains still.’ We designed three implicit studies to understand how people react or adapt to a rapidly changing world by testing whether verbal probability is better in expressing changeable uncertainty while numerical probability is better in expressing unchangeable uncertainty. We found that the ‘verbal-changeable’ combination in implicit tasks was more compatible than the ‘numerical-changeable’ combination. Furthermore, the ‘numerical-changeless’ combination was more compatible than the ‘verbal-changeless’ combination. Thus, a novel feature called ‘changeability’ was proposed to describe the changeable nature of verbal probability. However, numerical probability is a better carrier of changeless uncertainty than verbal probability. These results extend the domain of probability predictions and enrich our general understanding of communication with verbal and numerical probabilities. Given that the world around us is constantly changing, this ‘changeability’ feature may play a major role in preparing for uncertainty.